2013
DOI: 10.7783/kjmcs.2013.21.4.282
|View full text |Cite
|
Sign up to set email alerts
|

Change of Major Functional Components of Gastrodia elata Blume with Cultivation Conditions and Harvest Times

Abstract: S :Gastrodia elata Blume is a achlorophyllous orchid plant that has been used in traditional medicine to treat many human illnesses, such as vertigo, hemiplegia, and epilepsy. It contains three major pharmacological substances; gastrodin, ergothioneine, and vanillyl alcohol. Here we investigated the quantitative changes in those functional components by cultivation conditions and harvest times. The content of ergothioneine was different with cultivation areas, while gastrodin accumulated the higher levels than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…A recent study [ 9 ] reported 64 GEB components using various chromatography techniques. Among them, the most important phenolic compounds are gastrodin [4-β-d-glucopyranosyloxy) benzyl alcohol], 4-hydroxybenzyl alcohol (4-HBA), 4-hydroxybenzaldehyde, vanillin (4-hydroxy-3-methoxybenzaldehyde), vanillyl alcohol (4-(hydroxymethyl)-2-methoxyphenol), and vanillic acid (4-hydroxy-3-methoxybenzoic acid) [ 8 9 10 11 12 ]. New natural compounds have been recently found in GEB; bis (4-hydroxybenzyl) sulfide [ 2 ], Ergo [ 8 ], and diosgenin [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent study [ 9 ] reported 64 GEB components using various chromatography techniques. Among them, the most important phenolic compounds are gastrodin [4-β-d-glucopyranosyloxy) benzyl alcohol], 4-hydroxybenzyl alcohol (4-HBA), 4-hydroxybenzaldehyde, vanillin (4-hydroxy-3-methoxybenzaldehyde), vanillyl alcohol (4-(hydroxymethyl)-2-methoxyphenol), and vanillic acid (4-hydroxy-3-methoxybenzoic acid) [ 8 9 10 11 12 ]. New natural compounds have been recently found in GEB; bis (4-hydroxybenzyl) sulfide [ 2 ], Ergo [ 8 ], and diosgenin [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…, paralysis, vertigo, stroke, epilepsy, and dementia) [ 9 10 ]. A variety of bioactive compounds have been isolated from GEB, the most important ones are the phenolic compounds such as gastrodin, 4-hydroxybenzyl alcohol, 4-hydroxybenzaldehyde, vanillin, vanillyl alcohol, and vanillic acid [ 8 9 10 11 12 ]. It has been recently reported that bioactive compounds of GEB have an inhibitory potency for tyrosinase activity [ 13 14 15 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…최근 수확시기별, 재배 방법, 번식용으로 사용하는 자마의 종류에 따라 천마의 기능성물질 함량 또한 크게 차이 남이 보고 되어 있으나 아미노산에 대한 분석은 미 흡한 실정이다 (Kim and Park 2013). 아미노산은 생물의 몸을 구성하는 중요한 단백질 구성 요소이며 신진 대사를 원활하게 하는데 절대적으로 필요 한 영양소이다.…”
unclassified